AUGMENTED REALITY-BASED LEARNING MEDIA TO IMPROVE STUDENTS' UNDERSTANDING OF THE MATERIAL MY PROVINCE IS PART OF THE REGION OF INDONESIA - Dendi Irawan; Devi Afriyuni Yonanda; Ryan Dwi Puspita (Jurnal Cakrawala Pendas, 2025)
The purpose of this study is to investigate how the use of Augmented Reality-based learning media can improve students' understanding of districts/cities and provinces in Indonesia. The background of this study is the low level of students' understanding of districts/cities and provinces in Indonesia. One innovation that has attracted attention is Augmented Reality, which integrates digital elements with physical reality. The methodology applied in this study is a qualitative approach with a case study design. Data were obtained through interviews, observations, and questionnaires distributed to students and teachers. This study involved sixth-grade students of SDN Sangiang II, with a focus on classes studying Pancasila Education regarding districts/cities and provinces as part of the Unitary State of the Republic of Indonesia. The results showed that the use of Augmented Reality-based learning media significantly improved students' understanding of districts/cities and provinces. Students who used Augmented Reality showed an average increase in their scores of 30% compared to students who learned with conventional methods. This study concluded that Augmented Reality-based learning media is an effective tool to improve students' understanding of the material "my province is part of the Unitary State of the Republic of Indonesia."